Psychological Well-Being Among People Living with HIV/AIDS: A Systematic Review of Psychosocial and Contextual Determinants - Roza, Defia; Sastra, Lenni (Frontiers on Healthcare Research, 2026)
Background: Advances in antiretroviral therapy have transformed HIV into a chronic condition, yet psychological well-being remains inadequately addressed. Persistent stigma, psychological distress, and social inequities continue to compromise holistic health among people living with HIV/AIDS. Objectives: This systematic review aimed to synthesize evidence on psychosocial and contextual determinants of psychological well-being among people living with HIV/AIDS and to identify implications for research and practice. Methods: A systematic literature review was conducted following PRISMA guidelines. Peer-reviewed studies examining psychological well-being, mental health, stigma, coping, social support, and psychosocial interventions among adults living with HIV/AIDS were identified across major databases. Ten eligible studies, including observational studies, intervention trials, and systematic reviews, were critically appraised and synthesized using a thematic approach. Results: Five interrelated themes emerged. HIV-related stigma consistently showed a negative association with psychological well-being across settings. High levels of depression and anxiety persisted despite antiretroviral treatment. Psychosocial resources, particularly social support, counseling, and adaptive coping, functioned as protective factors. Psychosocial interventions demonstrated beneficial but variable effects, with modest effect sizes and limited long-term evidence. Finally, psychological well-being was closely linked to behavioral outcomes, including treatment adherence and substance use, highlighting bidirectional relationships. Conclusion: Psychological well-being among people living with HIV/AIDS is shaped by multilevel psychosocial and structural factors. Integrating standardized mental health assessment, stigma reduction strategies, and context-sensitive psychosocial interventions into routine HIV care is essential to improve holistic outcomes. Such integration may enhance quality of life, resilience, and long-term engagement in care worldwide across health systems and sociocultural contexts globally.